Silk‐based microcarriers: current developments and future perspectives. Issue 8 (22nd September 2020) - Veiga, Anabela; Castro, Filipa; Rocha, Fernando; Oliveira, Ana
Abstract : Cell‐seeded microcarriers (MCs) are currently one of the most promising topics in biotechnology. These systems are supportive structures for cell growth and expansion that allow efficient nutrient and gas transfer between the media and the attached cells. Silk proteins have been increasingly used for this purpose in the past few years due to their biocompatibility, biodegradability and non‐toxicity. To date, several silk fibroin spherical MCs in combination with alginate, gelatin and calcium phosphates have been reported with very interesting outcomes. In addition, other silk‐based three‐dimensional structures such as microparticles with chitosan and collagen, as well as organoids, have been increasingly studied. In this study, the physicochemical and biological properties of these biomaterials, as well as the recent methodologies for their processing and for cell culture, are discussed. The potential biomedical applications are also addressed. In addition, an analysis of the future perspectives is presented, where the potential of innovative silk‐based MCs processing technologies is highlighted.